Efficacy and toxicity of SEAM (semustine, etoposide, cytarabine, and melphalan) conditioning regimen followed by autologous stem cell transplantation in lymphoma. Issue 1 (31st December 2022) - Zhang, Lihong; Yang, Haifei; Qian, Chongsheng; Zhou, Jihao; Zhu, Qian; Jiang, Yibin; Liu, Shuo; Chen, Xiaochen; Xu, Ting; Qu, Changju; Li, Caixia; Jin, Zhengming; et al.
ABSTRACT: Objectives: The aim of this retrospective study was to evaluate the safety and efficacy of SEAM regimen followed by auto-SCT in lymphoma. Patients and methods: We retrospectively reviewed the records of patients with lymphoma who underwent auto-SCT with SEAM conditioning regimen from January 2010 to June 2018 at our centre. In total, 97 patients were analysed. Results: The median time to neutrophil engraftment and platelet engraftment was 9.5 days (range, 7–15 days) and 12 days (range, 7–25 days), respectively. Grade 3–4 nausea/vomiting, mucositis and diarrhoea were observed in 21.6%, 36.1%, and 11.3% of patients, respectively. Treatment-related mortality at 100 days occurred in 2 patients (2.1%). After a median follow-up time of 53.9 months, the 3-year incidence of disease relapse or progression was 34%. The estimated progression-free survival and overall survival at 3 years were 62% and 75%, respectively. Compared with previous studies using BEAM as the conditioning regimen, this study shows that the SEAM regimen has a comparable efficacy and safety profile. Conclusions: The SEAM regimen is feasible and might be an ideal alternative to BEAM regimen for lymphoma auto-SCT.